The carrier’s liability for damage to cargo in multimodal transport with special focus on the Rotterdam Rules - Ciok, Patryk (Studia Iuridica Toruniensia, 2017)
One of the most striking manifestations of the development of international transport is the increased importance of multimodal transport. Its characteristic feature is the use of at least two different modes of transport on one journey between different countries. One of the most distinctive legal problems in this context is the overlapping of legal regimes of the carrier’s liability regarding different types of transport, for example, by sea and by road. In maritime transport, attempts have been undertaken to solve this specific problem by adopting the Convention on Contracts for the International Carriage of Goods Wholly or Partly by Sea, commonly referred to as the Rotterdam Rules (RR), in 2008. This paper focuses on the development of maritime conventions as well as regulations related to the problems indicated. Another essential issue is the relation of the RR to the unimodal conventions governing the carrier’s liability in other modes of transport, especially in transport by road, by rail and by inland waterways. The impact of the RR on the Polish legislation and potential changes in the case of the RR’s ratification by Poland shall be also outlined.